ANTESEDENS DARI MISSED NURSING CARE - Elson Elson; Oscar Jayanagara (JMBI UNSRAT (Jurnal Ilmiah Manajemen Bisnis dan Inovasi Universitas Sam Ratulangi)., 2022)
This study was conducted to determine the antecedents of missed nursing care with nurse practice environment, job satisfaction, job burnout, patient safety culture dan nurse teamwork. This research is a quantitative study with cross-sectional design. Purposive sampling was done with a total of 128 respondents. This study was analyzed using PLS-SEM. The results of this study are job satisfaction and patient safety culture have an inversely significance impact on missed nursing care. In contrast, there is no significant impact of nurse practice environment and nurse teamwork on missed nursing care. However, we did find that job satisfaction mediates the negative relationship between nurse practice environment and nurse teamwork and missed nursing care. Job burnout has the most impact to missed nursing